Nitrification of high-strength ammonium landfill leachate with microbial community analysis using (FISH). - Yusof, Norjan; Hassan, Mohd Ali; Phang, Lai Yee; Tabatabaei, Meisam; Othman, Mohd Ridzuan; Mori, Masatsugu; Wakisaka, Minato; Sakai, Kenji; Shirai, Yoshihito (Sage Publication, 2011)
Nitrification of mature sanitary landfill leachate with high-strength of N_NHþ 4 (1080–2350mg L_1) was performed in a 10 L continuous nitrification activated sludge reactor. The nitrification system was acclimatized with synthetic leachate during feed batch operation to avoid substrate inhibition before being fed with actual mature leachate. Successful nitrification was achieved with an approximately complete ammonium removal (99%) and 96% of N_NHþ 4 conversion to N_NO_3 . The maximum volumetric and specific nitrification rates obtained were 2.56 kg N_NHþ4 m_3 day_1 and 0.23 g N_NHþ4g_1 volatile suspended solid (VSS) day_1, respectively, at hydraulic retention time (HRT) of 12.7 h and solid retention time of 50 days. Incomplete nitrification was encountered when operating at a higher nitrogen loading rate of 3.14 kg N_NHþ 4 m_3 day_1. The substrate overloading and nitrifiers competition with heterotrophs were believed to trigger the incomplete nitrification. Fluorescence in situ hybridization (FISH) results supported the syntrophic association between the ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria. FISH results also revealed the heterotrophs as the dominant and disintegration of some AOB cell aggregates into single cells which further supported the incomplete nitrification phenomenon.